Susceptibility of nutria (Myocastor coypus) to Trichinella infection: biological aspects - Moretti A.; Piergili Fioretti D.; Grelloni V.; Marini C.; Leonardi L.; Velatta F. (Parasite, 2001)
Experimental infections with three different species of Trichinella in nutria in order to evaluate the susceptibility and the role of these rodents in the spreading of parasitosis in nature were carried out. The nutria is present in many italian wet areas and its distribution is expanding. The nutria meat is utilized as food in different countries and is retained responsible for trichinellosis in man. Two groups of ten animals were infected per os with 500 and 5,000 (n. 10) infective larvae of T. britovi; an additional study was arranged with two groups of animals infected with 5,000 larvae of T. spiralis and T. pseudospiralis, respectively. After 45 days, all animals were slaughtered and samples of different muscles were processed by standard artificial digestion and by routine histological methods. Serological investigations (specific IgG) have been carried out on sera samples by employing a monoclonal blocking ELISA. The animals showed a significant susceptibility to the infection with all species of tested Trichinella and immunological reactivity. Data obtained are discussed.